Application of composite disease activity scores in psoriatic arthritis to the PRESTA data set. Issue 3 (11th October 2011) - FitzGerald, Oliver; Helliwell, Philip; Mease, Philip; Mumtaz, Aizad; Coates, Laura; Pedersen, Ronald; Nab, Henk; Molta, Charles
Abstract : Objective: This study aimed to compare the performances of the Modified Composite Psoriatic Disease Activity Index (mCPDAI) and the Disease Activity index for PSoriatic Arthritis (DAPSA) in an interventional study of etanercept in psoriatic arthritis. Methods: The components of the CPDAI and DAPSA were extracted using PRESTA ( Psoriasis Randomized Etanercept STudy in subjects with psoriatic Arthritis ) study data. Data for four of the five domains of the CPDAI—thus an mCPDAI—were available: joints, skin, dactylitis and enthesitis (spinal involvement was not assessed). Domains in the calculation of DAPSA were subjected to global assessment of pain, swollen and tender joint counts, and C reactive protein. Subjects were randomised to etanercept 50 mg weekly (n=373) or 50 mg twice weekly (n=379) for 12 weeks; all subjects then received etanercept 50 mg weekly for 12 weeks. The performance of the scores at baseline and on weeks 12 and 24 was compared between the two treatment regimens. Results: The mCPDAI and DAPSA could distinguish response to treatment comparing baseline and 12-week or 24-week values (p<0.0001). The mCPDAI, not DAPSA, could distinguish response between the two treatment groups at 12 weeks (p=0.0492), but not at 24 weeks. All domains evaluated contributed to the data variability of the mCPDAI; the most significant were dactylitis (r=0.64) and enthesitis (r=0.60). Conclusion: In psoriatic arthritis with severe skin involvement, the mCPDAI was able to distinguish treatment response between the two etanercept doses. DAPSA, while demonstrating improvement in both groups over time, was unable to distinguish response between the different doses of etanercept. Further studies are needed to confirm the sensitivity of both indexes.